THE ROLE OF SWAMI SIVANANDA JI IN THE CONTEXT OF TEACHER EDUCATION AND STUDENT SUCCESS - Pant, Reeta; Jain, Vinod Kumar (International Journal of Research -GRANTHAALAYAH, 2025)
India has long been a fountainhead of spiritual wisdom, nurturing countless visionaries who have shaped its cultural and philosophical landscape. Among them, Swami Sivananda Saraswati (1887–1963) emerges as a towering figure, whose synthesis of spirituality and practical service offers profound insights for the field of education. A trained medical doctor turned spiritual master, Swami Sivananda founded the Divine Life Society in 1936 in Rishikesh to promote a life of selfless service, spiritual discipline, and integrated education. This paper explores his contributions with specific emphasis on their implications for teacher education and student success. Swami Sivananda’s philosophy, grounded in Vedanta and yoga, emphasizes character formation, ethical living, and holistic development—ideals increasingly acknowledged as fundamental to 21st-century education. By analyzing his writings, teachings, and institutional work, the paper presents a framework for contemporary educational reform centered on spiritual awakening and human values.